First identification of metallo-beta-lactamase-producing Pseudomonas aeruginosa in the Czech Republic - Hrabák, J; Fridrichová, M; Stolbová, M; Bergerová, T; Zemlickova, H; Urbaskova, P (Euro surveillance, 2009)
Since 2005, invasive isolates of Pseudomonas aeruginosa have been collected in the Czech Republic as part of the European Antibiotic Resistance Surveillance System (EARSS). Forty-eight microbiology laboratories throughout the country including approximately 81% of the population provide consecutive isolates from blood and cerebrospinal fluid. Surprisingly, no metallo-beta-lactamase (MBL) was found in 1,259 invasive isolates tested over the past three years until the detection of two MBL-producing strains in mid-2008. Both strains were isolated from patients hospitalised in one regional hospital. The MBL was identified as IMP-7, which had been seen previously in Canada, Japan, Malaysia and Slovakia.
Keywords: druhová specificita; pseudomonádové infekce; Male; Česká republika; Pseudomonas Infections; beta-Lactamases; Adult; Aged; dospělí; mužské pohlaví; senioři; beta-laktamasy; Species Specificity; Czech Republic; lidé; Pseudomonas aeruginosa; ženské pohlaví; Humans; Female